2014
DOI: 10.1186/2044-5040-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Post-natal induction of PGC-1α protects against severe muscle dystrophy independently of utrophin

Abstract: BackgroundDuchenne muscle dystrophy (DMD) afflicts 1 million boys in the US and has few effective treatments. Constitutive transgenic expression of the transcriptional coactivator peroxisome proliferator-activated receptor gamma coactivator (PGC)-1α improves skeletal muscle function in the murine “mdx” model of DMD, but how this occurs, or whether it can occur post-natally, is not known. The leading mechanistic hypotheses for the benefits conferred by PGC-1α include the induction of utrophin, a dystrophin homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 63 publications
2
44
0
Order By: Relevance
“…Activation of some of these transcriptional regulators, such as ERRγ (59), the androgen receptor (60), PPARδ (61), and the PGC-1 coactivators (62,63), have also been shown to improve pathology in animal models of DMD. These observations support the contention that gene regulatory pathways such as the GR-KLF15 axis ameliorate DMD via modulation of muscle metabolic programming and add to an emerging body of evidence that defines intimate functional relationships between KLF family members and nuclear receptors (23, 24, 64-66).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of some of these transcriptional regulators, such as ERRγ (59), the androgen receptor (60), PPARδ (61), and the PGC-1 coactivators (62,63), have also been shown to improve pathology in animal models of DMD. These observations support the contention that gene regulatory pathways such as the GR-KLF15 axis ameliorate DMD via modulation of muscle metabolic programming and add to an emerging body of evidence that defines intimate functional relationships between KLF family members and nuclear receptors (23, 24, 64-66).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic stimulation of the phenotypic modifier AMPK with the pharmacologic agonist 5-aminoimidazole-4-carboxamide-1-␤-D-ribofuranoside (AICAR) elicited numerous favorable adaptations in dystrophic muscle in the absence of any alterations in utrophin A expression (48). Furthermore, transgenic induction of the slow, oxidative myogenic program via skeletal muscle-specific overexpression of estrogen-related receptor-␥, PGC-1␣, or PGC-1␤ in mdx mice resulted in structural and functional improvements in the dystrophic pathology without any change in utrophin A content (10,40). Independent of utrophin A, the putative reason(s) for the enhanced dystrophic resistance associated with the pharmacologic or transgenic induction of the slow, oxidative myogenic program is(are) currently unknown but could be related to numerous factors such as differential sarcolemmal protein composition, oxygen transport and utilization capabilities, intracellular calcium dynamics, contractile apparatus, molecular signaling infrastructure, and autophagy (36,37).…”
Section: MDXmentioning
confidence: 99%
“…The generation of muscle-specific transgenic or knockout dystrophic animals for factors such as GCN5, SIRT1, or AMPK would certainly advance our understanding of the molecular pathways involved in RSV-induced adaptations. To this end, studies in which these technologies have been implemented with PGC-1␣ and PGC-1␤ have expanded our knowledge with respect to the role of these coactivators in mediating neuromuscular plasticity (10,26).…”
Section: MDXmentioning
confidence: 99%
“…The protection has widely been presumed to result from the strong PGC-1α-mediated induction of neuromuscular junction genes and, in particular of utrophin, a homolog of dystrophin that is known to be protective in DMD models. However, we recently generated mice with muscle-specific expression of peroxisome proliferator-activated receptor gamma coactivator 1-β (PGC-1β), a homolog of PGC-1α, and found that PGC-1β did not induce neuromuscular junction (NMJ) genes or utrophin itself and yet was equally protective against dystrophy in the mdx model [14]. This suggested that utrophin was not the key mediator of protection in the PGC-1α transgenic mice.…”
Section: Introductionmentioning
confidence: 99%
“…We formally tested this notion by crossing the PGC-1α-expressing mice into an mdx /utrophin −/− background, which at baseline reveal much more pronounced dystrophy, including blunted growth, kyphosis, and early lethality. PGC-1α significantly improved the dystrophic phenotype of these mice, including early lethality [14]. PGC-1α thus potently protects against dystrophy, but not via utrophin.…”
Section: Introductionmentioning
confidence: 99%